2011
DOI: 10.3324/haematol.2010.030577
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of nuclear factor- B family genes are associated with development of multiple myeloma and treatment outcome in patients receiving bortezomib-based regimens

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThe nuclear factor-κB pathway is an important signaling pathway activated in multiple myeloma cells. Bortezomib inhibits nuclear factor-κB activation and is an important antimyeloma agent. Nevertheless, patients treated with this drug eventually relapse. We hypothesized that the nuclear factor-κB pathway may be associated with multiple myeloma and patients' responses to bortezomib. Design and MethodsIn this study we analyzed 26 polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 48 publications
2
41
0
1
Order By: Relevance
“…This distinctive and relative new group of polymorphisms is called miRSNPs (8). Although singlenucleotide polymorphism (SNP) in drug metabolic enzymes, DNA repair, or MDR1 have been described in association with prevalence, response to treatment, progression-free (PFS) and overall survival (OS) in multiple myeloma (9,10), no studies have been reported to date with miRSNPs in multiple myeloma. This novel class of SNPs opens a new area of research in cancer biology and clinical oncology.…”
Section: Introductionmentioning
confidence: 99%
“…This distinctive and relative new group of polymorphisms is called miRSNPs (8). Although singlenucleotide polymorphism (SNP) in drug metabolic enzymes, DNA repair, or MDR1 have been described in association with prevalence, response to treatment, progression-free (PFS) and overall survival (OS) in multiple myeloma (9,10), no studies have been reported to date with miRSNPs in multiple myeloma. This novel class of SNPs opens a new area of research in cancer biology and clinical oncology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the A allele of the rs11160707 SNP was associated with better progression-free survival [233], and the authors suggested that this polymorphism may correlate with disrupted TRAF3 activation. Hence, the indicated polymorphisms may be promising for oncogenomic studies.…”
Section: Tnf Receptor-associated Factor (Traf1-traf6) Gene Polymorphimentioning
confidence: 98%
“…The only study analyzing the association of TRAF3 SNPs with cancer risk was conducted by Du et al [233], who reported that the A allele of the rs7143468 polymorphism is related to higher multiple myeloma (MM) risk, whereas the A allele of the rs12147254 polymorphism, conversely, correlates with lower MM risk. In addition, the A allele of the rs11160707 SNP was associated with better progression-free survival [233], and the authors suggested that this polymorphism may correlate with disrupted TRAF3 activation.…”
Section: Tnf Receptor-associated Factor (Traf1-traf6) Gene Polymorphimentioning
confidence: 99%
“…An association between the carriers of the G allele for the -8C/G SNP in the 20S proteasome subunit coding gene PSMA6 and a better 5-year OS has been also shown (135). Recently, Du et al evidenced the association of the carriers of the A allele of the TRAF3 SNP rs11160707 with an improved PFS, while the variant alleles for two NFKB2 SNPs (rs12769316 and rs1056890) were associated, respectively, with an increased and a decreased OS (93).…”
Section: Role Of Snps In Therapy Outcome and Survivalmentioning
confidence: 99%
“…The activation of the nuclear transcription factor NF-κB is thought to be one of the most important factors to enhance cell proliferation in MM pathogenesis (89,90). The minor alleles of SNPs in genes related to the NF-κB pathway, such as the inhibitor IκBα (rs2233406, rs3138054, rs2233419) and the transcriptional activator TRAF3 (rs12147254) have been associated with a protective effect on MM development (91)(92)(93). Several polymorphisms in genes related to insulin metabolism resulted associated with MM risk.…”
Section: Genetic Risk Factors In Multiple Myelomamentioning
confidence: 99%